Recent advances in the Biosynthesis of Zirconium Oxide Nanoparticles and their Biological Applications (Baghdad Science Journal, 2023)
A critical milestone in nano-biotechnology is establishing reliable and ecological friendly methods for fabricating metal oxide NPs. Because of their great biodegradable, electrical, mechanical, and optical qualities, zirconia NPs (ZrO2NPs) attract much interest among all zirconia NPs (ZrO2NPs). Zirconium oxide (ZrO2) has piqued the interest of researchers throughout the world, particularly since the development of methods for the manufacture of nano-sized particles. An extensive study into the creation of nanoparticles utilizing various synthetic techniques and their potential uses has been stimulated by their high luminous efficiency, wide bandgap, and high exciton binding energy. Zirconium dioxide nanoparticles may be used as antimicrobial and anticancer agents in food packaging. In response to the growing interest in nano ZrO2, researchers invented and developed methods for synthesizing nanoparticles. ZrO2 nanocomposites with various morphologies have recently been created using biological (green chemistry) methods. Microbes and plants both contribute to the production of zirconia in the laboratory. Capping and stabilizing agents are provided by the biomolecules found in plant extracts, whereas microorganisms provide enzymes as capping and stabilizing agents (intracellular or extracellular). It is possible to analyze the nanoparticles produced using a variety of analytical approaches, including ultraviolet-visible spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FT-IR). When applied to bacteria (both Gram-positive and Gram-negative) and fungi, ZrO2NPs show promising antibacterial capabilities. Normal and malignant cells are sensitive to ZrO2 nanoparticles, which can be explained by the generation of reactive oxygen (ROS). This work discusses and describes many ways of producing ZrO2 nanoparticles, their properties, and various application possibilities.